Peran Orang Tua Dalam Menumbuhkan Fitrah Anak Melalui Interaksi Sehari-Hari - Masganti Sit; Alya Khairani; Fitria Ningsih; Wadhah Nabilah HSB (Mathematics Education Study Program, 2025)
A child's innate nature is an innate potential bestowed by Allah SWT upon His people. This nature must be nurtured and developed so that the child becomes an individual with commendable morals and good character. The research method used was a qualitative approach with data collection techniques such as observation, interviews, and documentation. The study results indicate that warm interactions built by parents and the habituation of commendable behavior towards children play a significant and crucial role in developing their innate nature. Therefore, a child's innate nature and character can develop optimally if parents can create a positive interaction accompanied by Islamic values and are consistent in every aspect of their child's development